Financializing The Public Utilities of New Urban Areas in Hanoi: When State Schools No Longer Are The Key Factor in The Residential Unit Design Concept - Tran, Minh-Tung; Chu, Ngoc-Huyen; Phan, Tien-Hau (International Journal of Sustainable Construction Engineering and Technology, 2024)
Since 1986, the Doi Moi policy in Vietnam has changed the State’s role from monopolizing the creation of new residential areas, including housing with state service facilities, to decentralizing the private economic sectors to participate in the housing production market. School has always been people’s top concern when buying a house and establishing their new life in new urban area projects introduced into Hanoi since the late twentieth century. The theories of residential units in urban form management also emphasize this institution’s central role in bringing social community improvements through the physical space. However, the financialization of housing and the ‘socialization’ of education, which are essentially privatization, have obscured the neighborhood-level school’s role by the profits from spatial production, making the urban form unstable and dysfunctional. A review of a residential unit concept that is more adapted to the local context to ensure a win-win between actors having the right to the city is necessary for spatial and social sustainability in new urban areas.